AlGaInAs/InP Based Five & Three Quantum Wells Mode Locked Laser Diodes: A Comparative Study - Akbar, Jehan; Hanif, Muhammad; Naeem, Muhammad Azhar; Abid, Kamran (Elektronika ir Elektrotechnika, 2020)
Comparison of performance of semiconductor mode-locked laser diodes fabricated using AlGaInAs/InP material containing 5 and 3 quantum wells (QWs) inside the active region is reported. The simulations and experimental results show that lasers containing five QWs materials produce larger beam divergence and temporally broader optical pulses. For improvement in the mode-locking of lasers and reducing the far-field pattern, the number of QWs inside the active region was decreased from five to three and a far-field decreasing layer along with a thick spacer layer were introduced in the n-cladding region of epitaxial material. Before growing the material, simulations were carried out to optimise the design. The lower optical confinement factor and higher gain saturation energy of three QWs based mode-locked lasers provide higher average and peak output power, reduced and symmetric far-field pattern, better radio frequency (RF) spectra, shorter optical pulses, and stable optimal mode-locking for a wide range of gain current and saturable absorber reverse voltage.